Project Report on Multiphameter Monitoring System for Coalmines based on Wireless Sensor Network Technology - GURURAJ, ASHWINI P and SATISH K N (2010)
INTERNAL GUIDE: M KRISHNAMOORTHY, MVJCE
Keywords: Wireless Sensor Network Technology